Terminalia arjuna flowers: Secondary metabolites and antifungal activity - Ahlam Hashem Elwekeel; Elham Amin; Ahmed Khairallah; Abeer Sayed Moawad (Faculty of Pharmacy, Mahidol University, 2022)
Fungal pathogens are able to cause serious infections to human. Candidiasis caused by Candida species and pulmonary aspergillosis caused by Aspergillus fumigatus may occur as secondary complication in immunocompromised patients. Meanwhile, biologically guided isolation of bioactive constituents from natural sources represents a promising strategy in drug discovery process. In this concern, the antimicrobial screening of 11 plants collected from Egypt was performed against several microbes. Terminalia arjuna flower extract was among the most active extracts against C. albicans. The antifungal potential of n-hexane, dichloromethane (DCM), ethyl acetate (EtOAc) fractions of T. arjuna flower were tested against C. albicans, A. fumigatus and Fusarium avenaceum. Results revealed a potent activity of EtOAc extract against C. albicans (100% inhibition, MIC=7.81 µg/mL). Chromatographic investigation of T. arjuna flower afforded nine compounds; β-sitosterol (1), stigmasterol (2), β-sitosterol-3-O-β-D-glucopyranoside (3), rosamultin (4), niga-ichigoside Fl (5), luteolin (6), apigenin (7), gallic acid (8) and methyl gallate (9). The structures of the isolated compounds were elucidated using different spectroscopic techniques especially 1D and 2D NMR. Among the isolated compounds, the two triterpenoid glycosides (4) and (5) have not been previously tested for antifungal potential. The current study indicated moderate activity of rosamultin (4) and niga-ichigoside Fl (5) (MIC 250 µg/mL) against C. albicans.